Health care for the poor in Latin America and the Caribbean - Mesa-Lago, Carmelo (PAHO Washington, D.C.US, 1992)
Reviews problems confronted by the health care systems in Latin America and the Caribbean at the turn of the 1980's; analyzes their current and potential capacity to provide adequate health protection for the poor; assesses the public and private efforts to five countries to fulfill that goal; and offers recommendations for the Region.